Azure app service web apps configuring and troubleshooting : LiveLessons - Cheshire, Jim (LiveLessons, 2017)
"Azure App Service is a popular and fast-changing technology that makes it easy to start a website in minutes. After you've created your site, you'll want to explore more advanced features, such as SSL certificates, custom domain names, authentication, deployment slots, and more. You might also encounter problems such as errors, a slow website, or slow pages. In this course, you learn how to deal with all these configuration and troubleshooting scenarios, and by the end of the course, you'll be an expert in Web Apps running on Azure App Service."--Resource description page.